An empirical study of investment evaluation and benefits realization methodologies adoption in B2B E-commerce for the digital TV industry - Lin, K.; Sun, S.; Hu, W.; Lin, Chad (Department of Information Management, National Chi Nan University, 2008)
With the advent of the knowledge-based economy, there has been a dramatic increase in B2B e-commerce investments by Taiwanese organizations in order to gain competitive advantage in their respective marketplace. However, these organizations have found it increasingly difficult to justify rising B2B e-commerce expenditures. They are often under enormous pressure to find a way to measure the contribution of their organizations’ B2B e-commerce investments to business performance, as well as to find reliable ways to ensure that the expected business benefits from these investments are eventually realized and delivered. Nevertheless, very few empirical studies have been conducted to examine the issue of benefits realization in B2B e-commerce investments. Given the financial stakes involved, better understanding of the financial implication of B2B e-commerce investment and its relationships with IT investment evaluation methodology, IT benefits realization methodology, IT maturity, and B2B e-commerce evaluation constraints in Taiwanese digital TV industry is warranted. A key contribution of the paper is the development of a B2B e-commerce management model that has the potential to assist the TV operators in adopting and managing digital TV as their commerce platform.